If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -4x + -2 = 2x + -14 + 6(1 + x) Reorder the terms: -6 + -2 + -4x = 2x + -14 + 6(1 + x) Combine like terms: -6 + -2 = -8 -8 + -4x = 2x + -14 + 6(1 + x) -8 + -4x = 2x + -14 + (1 * 6 + x * 6) -8 + -4x = 2x + -14 + (6 + 6x) Reorder the terms: -8 + -4x = -14 + 6 + 2x + 6x Combine like terms: -14 + 6 = -8 -8 + -4x = -8 + 2x + 6x Combine like terms: 2x + 6x = 8x -8 + -4x = -8 + 8x Add '8' to each side of the equation. -8 + 8 + -4x = -8 + 8 + 8x Combine like terms: -8 + 8 = 0 0 + -4x = -8 + 8 + 8x -4x = -8 + 8 + 8x Combine like terms: -8 + 8 = 0 -4x = 0 + 8x -4x = 8x Solving -4x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4x + -8x = 8x + -8x Combine like terms: -4x + -8x = -12x -12x = 8x + -8x Combine like terms: 8x + -8x = 0 -12x = 0 Divide each side by '-12'. x = 0 Simplifying x = 0
| 9x-(3x+21)=21 | | 2p+7p=52 | | -28+5x=2x+23 | | 84=(c+6)(-6) | | 2m+5n=pforn | | 6p+21=15p-6 | | -3-3n=3 | | -9+3a=36 | | 3x^2+22x+16= | | 3(y-2)=2(x+5) | | 5-6y+1=-1-2+1-4 | | -114+4x=-8x+42 | | 2(x+6)+5(2x+3)= | | 12x-(-9x)+38-(-25)-8x= | | 2+x/4=1 | | 2(2x-8)=22 | | 18.2z-1.63-7.7z=10.5z+1.53 | | 15-2x=-55 | | 2x+11=-18x+15 | | 100[0.08(n+6)]= | | -5k-5-2k=-12 | | -65+x=79-11x | | 15-2x=-15 | | 3=-7x-4 | | 10x+50=20x+10 | | 6r+2s-3(3r-5s)= | | 2x^2-8x+16= | | (7x-8)2Whenx=2 | | 1-7k-6=3-7k+4 | | -3(r+8)+12= | | Am-d=bform | | 2(1.2n+4)=4(.6n+1)+1 |